DETERMINANTS OF TAX SUBJECTS’ INTENTION TO PARTICIPATE IN THE VOLUNTARY DISCLOSURE PROGRAM - Yuniarwati, Yuniarwati; Siswanto, Halim Putera; Weruin, Urbanus Ura (International Journal of Application on Economics and Business, 2024)
The Voluntary Disclosure Program (PPS) is an opportunity for taxpayers to report/disclose tax obligations that have not been fulfilled voluntarily through payment of PPh based on asset disclosure. This program is expected to increase voluntary taxpayer compliance and is carried out based on the principles of simplicity, legal certainty and expediency. There are many factors that influence an individual taxpayer's intention to participate in PPS. Therefore, this research aims to examine the influence of tax sanctions, subjective norms and tax administration on individual taxpayers' intentions to participate in PPS. The population in this study is individual taxpayers who live in Tangerang City and the sample was chosen randomly among individual taxpayers who were willing to fill out the questionnaire. After calculations, there were 105 individual taxpayers participating in this research. The data was then analyzed using multiple linear regression using the SPSS version 25 software program. The results of data analysis showed that the first and third hypotheses were accepted, while the second hypothesis was rejected. Thus, tax sanctions and tax administration have a significant effect on individual taxpayers' intentions to participate in PPS, whereas this is not the case with subjective norms.